A Study Of Politeness Strategies Used By The Main Character In Persuasion Movie - Sholaikah , Fitri Nur (2012)
This study focuses on of politeness strategies found in Persuasion movie using Leech's theory. Someone should know how to use politeness strategy when they speak politely in English, because politeness universally exists but it is culturally bound. Therefore, the speakers and users of the language must be equipped with politeness formulas in speaking and must be aware of how to use politeness in different communicative acts in their daily life. It is purposed in making them to be able to communicate with the right language like where the language comes from. This research aims to investigate the following questions: (1) the types of politeness strategy are used by the main character, (2) to classify types of speech act contribute to the choice of politeness strategy, (3) to determine type of pragmatics scales contribute to the determining the degree of politeness? This research is a qualitative method. The data of this research are the excerpts of conversation which are produced by the main character with other characters containing politeness strategy in Persuasion movie. The collected data are analyzed by determining the type of speech act in each utterance. Then, the data are determined its type of maxim of politeness strategy based on the theory. Finally the degree of politeness used by the main character is determined using the measurement of pragmatics scale. The last, conclusion is drawn. The result of the study those are, 1) there are six maxims of politeness strategies which are used by the main character in Persuasion movie. Those six maxims are tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim and sympathy maxim. 2) there are four types of speech act which are applied in every maxim of politeness strategies, the first is commisive which is applied in politeness strategy of tact and generosity maxim, second is directive which is applied in politeness strategy of tact and generosity maxim, third is expressive which is applied in politeness strategy of approbation, modesty and sympaty maxim, and the last is assertive/ representative which is applied in politeness strategy of agreement maxim, 3) furthermore, the result shows that the main character of Persuasion movie follows the measurement of pragmatic scale to determine the degree of politeness strategy. Those pragmatics scales are cost-benefit, indirectness, optionality, power/ authority and social distance scale.